2023
DOI: 10.1038/s41598-023-31643-3
|View full text |Cite
|
Sign up to set email alerts
|

Statin protects men but not women with HIV against loss of muscle mass, strength, and physical function: a pilot study

Abstract: Statins are cholesterol-lowering drugs commonly used among people with HIV, associated with an increased risk of myopathies. Considering that cardiovascular disease, statin therapy, and sarcopenia are independently prevalent in people with HIV, clarity on the potential benefits or harms of statin therapy on muscle health is useful to provide insight into ways to maximize skeletal muscle health and minimize CVD risk in this population. We aimed to study the effects of statin therapy on strength, muscle mass, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Nevertheless, their presence raises questions regarding the holistic health benefit‐to‐burden, and underscores the gap in our understanding of mechanism of action for statins. Notably, in the context of HIV, a recent clinical trial reported differences based on biological sex in statin‐mediated protection in loss of muscle mass, strength, and physical function (Cárdenas et al, 2023 ).…”
mentioning
confidence: 99%
“…Nevertheless, their presence raises questions regarding the holistic health benefit‐to‐burden, and underscores the gap in our understanding of mechanism of action for statins. Notably, in the context of HIV, a recent clinical trial reported differences based on biological sex in statin‐mediated protection in loss of muscle mass, strength, and physical function (Cárdenas et al, 2023 ).…”
mentioning
confidence: 99%